KUASA KARAOKE : KAJIAN RUANG KARAOKE DALAM PEREBUTAN KUASA - nugrahanto (LIPI Press, 2022)
Activities in the karaoke room are not just singing, but also contentious arena to seek prestige and build social relations. This research uncovers the spatial practice of karaoke rooms, representation of karaoke rooms, karaoke as a representation room, and power struggles in karaoke rooms. This research using the theory of Lefebvre related to the production of space. Karaoke room from the side of abstract space and absolute space cannot be separated from perception, conception, and the space it lives in. This research uses case study method. The researcher also uses a participatory observation approach because the researcher is involved in the community being studied. The results of this reseacrh indicate that with karaoke, it is easier for people to get night entertainment. This also undermines public perception regarding haunted areas in the region. The karaoke room is also used as a social space for people who have practical politics. At the same time, karaoke rooms are used to implement political strategies. The representation of karaoke rooms by the state is limited to singing with or without a guide in the room which can generate income for the state treasury. Karaoke guides and karaoke consumers compete with each other for power in the karaoke room; power from consumers to consumers, consumers to karaoke guides, and between karaoke guides themselves.